Estrategia de producción para aumentar el rendimiento en la planta industrial de la Empresa Emproforsa del cantón Quevedo, año 2014 - Daza Bravo, Sandro Arcadio (2015)
This research work entitled "STRATEGY TO INCREASE PRODUCTION PERFORMANCE IN INDUSTRIAL PLANT COMPANY CANTON EMPROFORSA Quevedo, YEAR 2014" examines the peculiarities of the structure of management applied to the production company, its impact on the performance and productivity, taking into account the weaknesses of. The specific objectives of the research were: Perform analysis of the situation and current performance of the production plant, identify the stages that have high percentages of waste, determine the causes of the high levels of waste in the production process and develop production strategy to improve the performance and productivity of the plant. The information gathering was done through appropriate techniques as represented: the survey interview; also benefited this and mediated through relevant instruments such as: camera and notebook. The study concluded that the brushing process is the highest percentage of waste generated, about 20.83% on average for all thicknesses of balsa wood that work on the ground, this situation leads to the average performance of the plant Industrial are in the 59.06%. In addition, high percentages of waste and poor performance of the plant are given primarily to excess cleaning or processing balsa wood in the process of brushing, saw table and edging. This research served to the effective development of a production strategy based on continuous improvement in the company EMPROFORSA Quevedo Canton in order to improve and enhance its performance.